Passive smoker during pregnancy is a risk factor of low birth weight - Kanda Izzatul Aini Ardelia; Gatut Hardianto; Djohar Nuswantoro (Majalah Obstetri dan Ginekologi, 2019)
Objectives: to analyze the relationship between passive smoker of pregnant women with low birth weight (LBW).Materials and Methods: This study is an observational analytic research with case control design, which is LBW as case group and normal birth weight as control group. The location is in Wonokusumo Health Centre, Surabaya, period January 2016 – December 2017. Study sample was 68, consisting of 34 cases and 34 controls. The dependent variable is LBW, while the inde-pendent variable is passive smoking of pregnant women. Sample was excluded multiple births and congenital defects. To determine a significant level, the data collected will be tested with the statistical test Chi-square at significance level ?=0.05.Results: The results showed that a majority (61.5%) of passive smoker of pregnant women are cases. After Chi-square test obtained by value p=0.027 (p?0,05) and OR analysis obtained by 3.04 (CI 95% 1.117 – 8.274), which means there is a relationship between passive smoker of pregnant women with LBW.Conclusion: Passive smoker of pregnant women is relationship with decreased birth weight.